2014
DOI: 10.1002/asi.23106
|View full text |Cite
|
Sign up to set email alerts
|

Finding knowledge paths among scientific disciplines

Abstract: This paper uncovers patterns of knowledge dissemination among scientific disciplines. Although the transfer of knowledge is largely unobservable, citations from one discipline to another have been proven to be an effective proxy to study disciplinary knowledge flow. This study constructs a knowledge‐flow network in which a node represents a Journal Citation Reports subject category and a link denotes the citations from one subject category to another. Using the concept of shortest path, several quantitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 81 publications
0
43
0
1
Order By: Relevance
“…The topic‐to‐topic citation network was thus transformed into a distance‐based network through r e v e r s e _ f l o w _ w i d t h i j = 1 n u m b e r o f c i t a t i o n s f r o m j t o i . It shows that the more citations from one topic to another, the wider the knowledge flow (Yan, ). All 2,500 paths (i.e., 50*50 by including paths to themselves) were identified among the 50 topics through the Dijkstra algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…The topic‐to‐topic citation network was thus transformed into a distance‐based network through r e v e r s e _ f l o w _ w i d t h i j = 1 n u m b e r o f c i t a t i o n s f r o m j t o i . It shows that the more citations from one topic to another, the wider the knowledge flow (Yan, ). All 2,500 paths (i.e., 50*50 by including paths to themselves) were identified among the 50 topics through the Dijkstra algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, we count “ Applied Psychological Measurement+Psychology (miscellaneous) ” and “ Applied Psychological Measurement+Social Sciences (miscellaneous) ” as two individual entries. This treatment, also known as multiassignment, is consistent with prior journal‐level impact assessment (Yan, ; Yan, Ding, Cronin, & Leydesdorff, ), because it avoided the arbitrariness of assigning a journal to one of its few classifications. Despite its comprehensive coverage of science, social science, and humanity domains, a few limitations of ASJC should be noted: first, biomedical journals are more heavily represented in this schema (Guerrero‐Bote, Zapico‐Alonso, Espinosa‐Calvo, Gómez‐Crisóstomo, & de Moya‐Anegón, ); second, this schema has more detailed classification hierarchies for science domains than their social science counterparts (Yan, ; Yan & Zhu, ).…”
Section: Datamentioning
confidence: 63%
“…Finally, a study of knowledge paths between scientific disciplines is highlighted, based on data from the Web of Science, about citations between categories of subjects (Yan, 2014). The study concluded that the knowledge flow is easier from social sciences to sciences (life and biomedicine, physics, and technology) than in the opposite direction, which is attributed to the fact that the majority of the social sciences are more independent and primarily cite their own publications.…”
Section: Discussionmentioning
confidence: 99%